Inequality and Crisis: Conspicuous Consumption as the Missing Link in the Portuguese Case. Issue 1 (2nd January 2019) - Matos, Cristina
Abstract: Portuguese household debt increased above GDP between 2000 and 2007. This article uses conspicuous consumption to explain credit demand dynamics. The author develops an institutionalist framework and consider how rapid high inequalities and increasing top income share favored conspicuous consumption and climbing household debt.